Evaluating EMR Adoption and Its Effect on Organizational Performance: A Quantitative Study Using SEM-PLS in Type-C Hospitals in Kupang City - Mahasar Reinheart F. Damanik; Aloysius Liliweri; William Djani; I Putu Yoga Bumi Pradana (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: This study aims to identify key determinants influencing EMR adoption and measure their subsequent impact on organizational performance in Type-C hospitals, emphasizing internal organizational factors, user acceptance, and adaptability to healthcare policy dynamics. With persistent implementation gaps in low-resource settings despite national mandates our objective was to explore user-centered determinants of EMR success and address the shortcomings of top-down health digitalization strategies in developing countries. Methods: This cross-sectional explanatory study involved a survey-based quantitative design conducted across three Type-C hospitals in Kupang City, Indonesia, between January and March 2024. A total of 282 healthcare professionals, selected using stratified random sampling, participated in the study. Data were collected using a validated Likert-scale questionnaire measuring variables such as human capital, task-technology fit, and system acceptance. Given the non-interventional nature of this study, adherence to ethical research standards including voluntary informed consent, and obtained administrative approvals from relevant local government authorities, formal ethical approval was waived as per prevailing national guidelines. Results: The primary outcome of the study was the identification of key drivers of EMR acceptance, with human capital (? = 0.205; p < 0.001), task-technology fit (? = 0.203; p = 0.001), and effort expectancy (? = 0.176; p < 0.001) showing significant influence. Additionally, user satisfaction was found to mediate the relationship between acceptance and organizational performance (? = 0.728; p < 0.001). External variables such as perceived cost and government policy showed no significant effect (p > 0.05). The strongest indirect effect on performance was recorded via the pathway: Acceptance ? Satisfaction ? Performance (? = 0.394; p < 0.001). Conclusion: In conclusion, our study contributes to the understanding of EMR adoption in resource-constrained health systems by highlighting the dominant role of internal capabilities over external mandates. This research provides insights into the importance of user satisfaction and system alignment in shaping digital health success. Future studies should explore longitudinal impacts and the role of organizational culture, ultimately advancing knowledge in the field of international health informatics.